The Influence of E-Learning Media in the PBL Approach to Participants' Interest and Learning Achievement - July Kurniawati; Retno Danu Rusmawati; Hartono Hartono (Departement of Mathematics Education, 2023)
The objectives of this research are (1) to find out and describe the effect of the use of e-learning media in the PBL approach on student achievement, (2) to know and describe the effect of student interest in learning on student achievement, and (3) to know and describe the significant interaction between the use of e-learning media in the PBL approach with interest in learning on student achievement in elementary schools (SDN). This study used an experiment where the research group was divided into two classes, namely classes using e-learning media in the PBL approach and without the PBL approach and with high learning interest and low learning interest. This study used the 2-way Anova data analysis technique. Based on the calculation of the 2-way analysis obtained: (1) There is a significant difference in the use of e-learning media in the PBL approach to student learning achievement, (2) there is a significant difference in learning interest on student learning achievement, and (3) There is a significant interaction significant use of e-learning media in the PBL approach and interest in learning on student achievement. Based on the results of this study, it was concluded that by using e-learning media in the PBL approach and learning interest in learning achievement of students can improve.